2011
DOI: 10.1177/0363546511417172
|View full text |Cite
|
Sign up to set email alerts
|

Cocultures of Adult and Juvenile Chondrocytes Compared With Adult and Juvenile Chondral Fragments

Abstract: Background The use of allogenic juvenile chondrocytes or autologous chondral fragments has shown promising laboratory results for the repair of chondral lesions. Hypothesis/Purpose The purpose of the study was to evaluate in vitro the extracellular matrix production of mixed adult/juvenile cultures of both chondrocytes (part 1) and minced cartilage fragments (part 2). The authors hypothesized that juvenile chondrocytes would not affect matrix production when mixed with adult chondrocytes or cartilage fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 31 publications
2
59
0
Order By: Relevance
“…This neoformed tissue was mostly originating from the migrated chondrocytes and showed features similar to those of articular cartilage, such as the overall predominance of collagen type II staining. These in vitro results are consistent with two previously published studies by Bonasia et al (2011), in which adult and juvenile chondral fragments were cultured on a hyaluronic acid scaffold, and Lu et al (2006). In the latter, human and bovine cartilage fragments were used both in explant cultures and in a heterotopic implant in SCID mice, after being seeded in scaffolds made of polyglycolide/ non-woven felt or polyglycolide/polycaprolactone foam reinforced with polydiaxanone mesh, with a coating of fibrin glue.…”
Section: A Marmotti Et Al One Stage Osteochondral Repair In Goat Modelsupporting
confidence: 93%
“…This neoformed tissue was mostly originating from the migrated chondrocytes and showed features similar to those of articular cartilage, such as the overall predominance of collagen type II staining. These in vitro results are consistent with two previously published studies by Bonasia et al (2011), in which adult and juvenile chondral fragments were cultured on a hyaluronic acid scaffold, and Lu et al (2006). In the latter, human and bovine cartilage fragments were used both in explant cultures and in a heterotopic implant in SCID mice, after being seeded in scaffolds made of polyglycolide/ non-woven felt or polyglycolide/polycaprolactone foam reinforced with polydiaxanone mesh, with a coating of fibrin glue.…”
Section: A Marmotti Et Al One Stage Osteochondral Repair In Goat Modelsupporting
confidence: 93%
“…The theory behind DeNovo NT is that juvenile chondrocytes have the potential with higher metabolic activity level to reproduce more hyaline cartilage than adult chondrocyte [81]. Several in vitro studies demonstrated that juvenile cartilage was superior to adult cartilage in terms of chondrogenesis [82][83][84]. However, no published animal studies have investigated the histological and structural behavior of particulate juvenile cartilage allograft implantation in osteochondral defects.…”
Section: Cartilage Allograftmentioning
confidence: 99%
“…4). Juvenile chondrocytes (<13 years old) have 100-fold increased ability to produce proteoglycans and have the potential to increase the ability of adult cartilage fragments to produce matrix [17,18]. These cells also do not stimulate an immunogenic response in vivo [17].…”
Section: Minced Cartilage Productsmentioning
confidence: 99%